Antioxidant and Cytotoxic Effect of Water Extract of Ananas comosus in Human Breast Cancer Cell Line - Widyanto, Rahma Micho; Halimah, Ririt Nafi'; Rahmi, Yosfi; Utomo, Budi; Proborini, Wahyu Diah; Yunimar, Yunimar (Journal of Islamic Medicine, 2020)
Background: Breast cancer is the most common type of cancer and the second leading cause of death in the world. One of the supporting therapeutic efforts to overcome cancer is through food, mainly fruits. Ananas comosus has been investigated for its potential as an anti-cancer. It is a source of antioxidants from the content of Vitamin C and flavonoids that work by capturing free radicals, resulting in inhibition of cancer cell proliferation.Objective :This study was conducted to determine the antioxidant activity and cytotoxicity of water extract of Ananas comosus on T-47D breast cancer cell lines.Method: The process of extracting pineapple flesh is done using water as a solvent, then tested its antioxidant activity using DPPH and cytotoxicity using MTT assay on T-47D.Result: IC50 value for antioxidant activity was 463.369 Î¼g / mL and the IC50 for the cytotoxicity assay was 488.003 Î¼g / mL.Conclusion : The water extract of Ananas comosus have very weak antioxidant activity and moderate cytotoxicity properties that have potential as chemo preventive agents in T-47D breast cancer cell lines.